Tingkat Gaya Hidup dan Potensi Kepesertaan Dana Pensiun pada Pekerja Muda di Jakarta - Syarifudin Yunus (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to describe the lifestyle and potential participation of financial institution pension funds (DPLK) among young workers in Jakarta. The study respondents included 42 young workers with various occupational backgrounds and income levels. The results showed that 46% of young workers have a low-cost lifestyle, so they stated that preparing for retirement funds early is important. Furthermore, 46% of respondents have the ability to save in DPLK with monthly contributions between Rp100,000–Rp300,000, 28% can contribute more than Rp300,000, while 26% can only set aside less than Rp100,000 per month. This level of awareness shows variations in financial readiness influenced by several factors. First, a still dominant consumptive lifestyle causes some young workers to delay retirement planning. Second, low financial literacy regarding pension funds makes them less aware of the benefits and urgency of DPLK participation. Third, the perception that retirement is still far away encourages delays, thus reducing commitment to active participation. To increase young worker participation, several strategies can be adopted, including relevant and contextual pension fund education, providing digital platforms that facilitate access, implementing incentive systems to attract interest, and positioning Pension Funds (DPLK) as part of a modern lifestyle. Furthermore, innovative ultra-micro DPLK products can reach workers with limited financial resources. If these strategic steps are implemented consistently, young worker participation in DPLK has the potential to increase significantly. Thus, pension funds in Indonesia can enter a